Fuzzy logic controller for controlling DC motor speed using MATLAB applications - Nur Azliza, Ali (2008)
The purpose of this project is to control the speed of DC motor by using fuzzy logic controller with MATLAB applications. The scopes includes the simulation and modeling of DC motor, implementation of fuzzy logic controller to actual DC motor and comparison between MATLAB simulation and experimental result. This research was about to introduce the new ability of estimating speed and control the DC motor. By using the controller, the speed can be tuned until it get similar to the desired output that user need. Data will be transferred from the controller to the DC motor using the DAQ card. Encoder will be used to detect speed error between the desired output and the measured output.